Chocolate frogs do not increase completion of parent survey: Randomised study. (13th June 2014) - Price, Anna MH; Coates, Cathy; Symeonides, Christos; Hiscock, Harriet; Smith, Libby; York, Elissa; Hennel, Sabine
Abstract Four months into a year‐long, national survey assessing parents' experiences of a child's diagnosis of autism spectrum disorder, our response fraction was only 23%. We aimed to determine whether including a chocolate incentive in the postal survey would increase the response fraction. Families enrolled between 15 March and 25 May 2012 were randomised to receive a chocolate frog versus no chocolate frog. Both groups received a written reminder and replacement survey 2 weeks after the survey was posted and up to two telephone reminders thereafter. We analysed the effect of the incentive using χ2 tests for the categorical response variable and t‐tests for the continuous reminder and length of response variables at the end of (i) randomisation and (ii) the study (1 November 2012). A total of 137 families were randomised in the 6‐week period. Parents who received an incentive were more likely to return a completed survey in the 6 weeks than those who did not (21% vs. 6%, P = 0.009). This effect faded by the end of the study (53% vs. 42%, P = 0.4). There were no differences between groups at either follow‐up in the number of reminders that parents received or the number of days it took parents to return the survey. Including a chocolate‐based incentive does not significantly increase response rate in a postal survey over and above standard reminder techniques like posting follow‐up survey packs or phoning families.